FAKTOR- FAKTOR YANG MEMPENGARUHI WANITA MELAKUKAN PEMERIKSAAN IVA - Simbolon, Marlina Lasmawati (Midwifery And Complementary Care, 2022)
Background: The number of cervical cancer cases ranks second in the world. Early sexual intercourse can increase the risk of developing cervical cancer. Cervical cancer is also associated with the number of sexual partners. Objective: This is to determine what factors influence women to do IVA at the Petatal Health Center, Batubara Regency Method: This type of research was an analytic survey with a cross-sectional design with a sample of 73 women at the Puskesmas Petatal, Batubara Regency. The research instrument used data analysis using the chi-square. Conclusion: There is no relationship between knowledge and IVA with p-value = 0.704. There is no relationship between attitude and IVA with p-value = 0.953. Conclusion: There is no relationship between knowledge and attitudes with the implementation of IVA.